Subjective Well-being and Mental Health During the Pandemic Outbreak: Exploring the Role of Institutional Trust - Lee, Sunwoo (Research on aging, 2022)
This study examined the relationship between material adversities due to pandemic crisis, institutional trust, and subjective well-being and mental health among middle-aged and older adults aged 50+ in Europe. The study used a cross-sectional design to examine Eurofound COVID-19 survey data collected from 27 European countries in April 2020. A total of 31,757 European middle aged and older adults aged 50 + were analyzed (Mean = 59.99, SD = 7.03). Analysis focused on the financial impact and material security in relation to pandemic lockdown, institutional trust (news media, police, national government, European Union, and healthcare system), and subjective well-being and mental health. Regression analysis indicated perceived insecurity in employment and housing, worsening finances, and difficulty paying for basic necessities were significantly related to respondents' life satisfaction, happiness, self-rated health, mental health index, and psychological distress. Institutional trust partially mediated the relationship between perceived adversities and subjective well-being and mental health.
Keywords: institutional trust; senioři; Cross-Sectional Studies; kontrola infekčních nemocí; Pandemics; Trust; důvěra; Europe; material and financial difficulty; SARS-CoV-2; Mental Health; Middle Aged; Disease Outbreaks; COVID-19; průřezové studie; mental health; epidemický výskyt choroby; Communicable Disease Control; duševní zdraví; Humans; pandemic; lidé středního věku; pandemie; Aged; subjective well-being; lidé